HUBUNGAN AKTIVITAS OLAHRAGA DENGAN KEJADIAN SINDROM PRAMENSTRUASI PADA REMAJA PUTRI SMAN 6 TANGERANG - Isramilda, Isramilda; Purwati, Kasih (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Â People do not realize the importance of living a healthy life by exercising, so many have put sports aside as life priorities. According to WHO 2018, around the world around 70% of adolescents do not do sports. When heading to adulthood, many things can affect the attitudes and behavior of adolescents so that they will have an impact on reproductive health. Like before menstruation, the symptoms that arise are discomfort that occurs for a short time and can become intense, this is called premenstrual syndrome. Sports activity is one of the factors that can relieve premenstrual syndrome. This research method is observational analytic with cross sectional approach which was conducted at SMAN 6 Tangerang in November. The sampling technique was simple random sampling with a total sample of 130 students. The research results were analyzed by using Chi-Square. The results of research on 130 respondents, showed that 18 students with mild PMS did regular exercise, 14 students (40%) who were irregular. There were 20 students with moderate PMS did regular exercise (32.8%) and 41 students (67.2%) who were irregular. Then, there were 8 students with severe PMS did regular exercise (20.5%), and 31 students (79.5%) who were irregular.Based on this research, there is a relationship between sports activity and the incidence of premenstrual syndrome in young women at SMAN 6 Tangerang